2009
DOI: 10.1111/j.1464-410x.2008.08260.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of renal oxidative stress and inflammatory response after lithotripsy

Abstract: OBJECTIVE To determine if the acute renal oxidative stress and inflammation after extracorporeal shock wave lithotripsy (ESWL), thought to be mediated by ischaemia, is most severe in the portion of the kidney within the focal zone of the lithotripter, and if these effects result primarily from ischaemic injury. MATERIALS AND METHODS Pigs (7–8‐weeks old) received either 2000 shock waves at 24 kV to the lower‐pole calyx of one kidney or unilateral renal ischaemia for 1 h. A third group (sham) received no treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 28 publications
(40 reference statements)
3
44
2
Order By: Relevance
“…Aksoy et al [5] reported an increase in MDA and nitric oxide in plasma and urine immediately after a shockwave session. However, as in the present study, neither a study by Clark et al [33] nor a previous study [34] found changes in LPO levels. For oxidative stress in the present study, there were only slight decreases in GSH and SOD at the 2-and 24-h follow-ups.…”
Section: Eswl Associated Injurycontrasting
confidence: 87%
“…Aksoy et al [5] reported an increase in MDA and nitric oxide in plasma and urine immediately after a shockwave session. However, as in the present study, neither a study by Clark et al [33] nor a previous study [34] found changes in LPO levels. For oxidative stress in the present study, there were only slight decreases in GSH and SOD at the 2-and 24-h follow-ups.…”
Section: Eswl Associated Injurycontrasting
confidence: 87%
“…While earlier studies focused on oxidative injury to the renal cortex (15), Clark et al showed that acute oxidative stress and infl ammation after SWL are highly localized to the renal medulla within the focus (F2) of the lithotripter (19). In our study we also observed that cortical and medullar collector tubules were more affected than glomeruli.…”
Section: Discussionsupporting
confidence: 63%
“…The role of these signaling molecules is communication between immune cells or other cells. They regulate inflammatory and immune responses (14). Interleukin-1ɑ (IL-1ɑ) and interleukin-6 (IL-6) are used to call pro-inflammatory cytokines due to their role in the inflammatory process.…”
Section: Introductionmentioning
confidence: 99%